Firkee Bachchon Ki — A Magazine for Early Grades - NIKALJE, VARADA M. (THE PRIMARY TEACHER, 2015)
Children respond eagerly and readily to reading material and illustrations within their range of comprehension. Short poems and tales, picture stories and drawings have the magical quality of making children fly imaginatively to an altogether different time and place (Amar, 1943). In India, children’s literature is about 150 years old; children’s magazines lesser than that. Children’s magazines is a relatively new genre that is slowly but surely catching up with the rest of the literary world. For very young children of Classes I and II, there is hardly any magazine of good quality and affordable range (Enciso et al., 2010). Firkee Bachchon Ki brought out by the National Council of Education Research and Training (NCERT) is one such magazine. Primarily meant for the children of Classes I and II, the contents of the magazine are diverse. It contains children’s creative writings contextualised in their daily life experiences, with relevant and detailed illustrations supporting the text. The themes of everyday life such as trees, family, food, pets and games constitute the main subject matter of the magazine. As such, the magazine provides children with appropriate and fascinating reading material in a simple format and more importantly, from a child’s perspective. These enable children to understand and appreciate the myriad things around them: nature, their surroundings, the detailing of objects and so on. Initially therefore the magazine was launched to address the deeply felt need to provide children of government schools with supplementary reading material. Earlier, Firkee Bachchon Ki was brought out on a trial basis and was unpriced. Four issues later, and with growing demand, the magazine is now priced and soon to be registered.